2019
DOI: 10.29244/jpsl.9.1.181-189
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Changes in Climate and Land Use on the Future Streamflow Fluctuation: Case Study Merangin Tembesi Watershed, Jambi Province, Indonesia

Abstract: Beside land use change, future climate change potentially alters streamflow fluctuation of a river basin in Indonesia. We investigated relative impact of changes in climate and land use on the streamflow fluctuation of a watershed in Jambi Province, Indonesia for future condition (2025). To account for the climate change, we simulated future rainfall and temperature scenarios using the downscaled rainfall and mean surface temperature of 24 CMIP5 GCM outputs with moderate scenario of RCP4.5. We used distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…The increase in the coverage of flood inundation areas was mainly caused by factors related to land degradation, such as lower soil infiltration and increased runoff due to the decrease of forest area, both upstream and downstream of the watershed. A low infiltration rate will increase the surface runoff component and, in turn, will also increase the peak discharge (Tarigan and Faqih, 2019). The simulation results of this model show the strong impact of land use change on the hydrological process in the Lower Cimanuk Watershed.…”
Section: Impact Of Changes In Land Use and Climate On Inundation Areamentioning
confidence: 83%
See 2 more Smart Citations
“…The increase in the coverage of flood inundation areas was mainly caused by factors related to land degradation, such as lower soil infiltration and increased runoff due to the decrease of forest area, both upstream and downstream of the watershed. A low infiltration rate will increase the surface runoff component and, in turn, will also increase the peak discharge (Tarigan and Faqih, 2019). The simulation results of this model show the strong impact of land use change on the hydrological process in the Lower Cimanuk Watershed.…”
Section: Impact Of Changes In Land Use and Climate On Inundation Areamentioning
confidence: 83%
“…They found that the inundation areas under future climates are expected to be larger than those produced by the present climate events. In other studies, the impacts of both climate and land use changes were shown to cause an increase in the maximum peak discharge in the Merangin Tembesi Watershed (Tarigan and Faqih, 2019) as well as an increase in runoff and a decline in base flow contribution to annual streamflow in the Cimanuk Watershed (Ridwansyah et al, 2020).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Meningkatnya aliran permukaan, naiknya urbanisasi serta penebangan hutan secara sembarangan merupakan faktor terpenting yang berkontribusi terhadap meningkatnya limpasan di wilayah DAS di utara Iran, dan pengembangan daerah pemukiman baru menyebabkan peningkatan paling signifikan pada limpasan (Zare et al, 2016). Perubahan terhadap elemen meteorologi dan sifat fisik daerah akan berdampak terhadap naik turunnya limpasan dan debit, sebagaimana hasil riset di daerah aliran sungai (DAS) Merangin Tembesi Jambi, bahwa perubahan LU menyebabkan penurunan 40% dari debit minimum di musim kemarau dan 65% peningkatan debit puncak maksimum di musim hujan (Tarigan & Faqih, 2019). Perubahan LU dari hutan ke non hutan dalam skala besar menyebabkan kerusakan lingkungan dan mengurangi fungsi hidrologis DAS Ciliwung-Bogor (Nuraidaa, Rachman, & Baskoro, 2016).…”
Section: Limpasan Puncakunclassified
“…The effect of climate change is heightened in sub-Saharan Africa partly due to low coping capabilities, poor preparedness and weak institutional capacity of detecting early warning (Debela et al, 2015). Consequently, increasing global warming easily affects the rainfall pattern, causes flooding, and leads to drought thereby contributing to production failure and relate to humanitarian crisis in the region (Kibue et al, 2015).In the tropical countries, in addition to changing land use pattern, climate change leads to significant water discharge fluctuation which in turn affects the livelihood of a huge population (Tarigan & Faqih, 2019).…”
Section: Introductionmentioning
confidence: 99%